How the alcohol industry fought against pregnancy warning labels in France. A press coverage analysis spanning 20 years - Millot, Ana; Serra, Martina; Gallopel-Morvan, Karine (Frontiers in Public Health, 2022)
Background Drinking alcohol while pregnant is dangerous for health. To inform on this issue, various countries have adopted pregnancy warning labels on alcoholic beverages, including France since 2007, where wine holds deep cultural consonance. The aim of this research was to analyze the arguments put forward by the alcohol industry (producers, distributors, wholesalers, allied industries, trade associations, social aspects and public relations organizations, councilors who publicly defend wine-sector interests) via the press in France: (1) in 2007 when pregnancy warnings were first implemented, and (2) in 2018 when larger pregnancy warnings to increase visibility were proposed but not adopted. Methods We used documentary method to analyze the arguments advanced by the alcohol industry in mainstream (national, regional and specialized) press in France from 2000 to 2020, using the Europresse documentary database. Quantitative analysis (number and trend curve of articles, mapping alcohol-industry actors who spoke in the press) and inductive thematic content analysis (analytical framework of the arguments identified) using NVivo software were carried out. Results We found a total of 559 relevant press articles in the database, of which 85 were included in the analysis. Peaks in number of publications were found to coincide with the warning label implementation and with the expansion-project schedule. A large majority of the arguments promoted by the alcohol industry contested the pregnancy warnings measure (very few were in favor). They argued that (1) pregnancy warnings were a questionable measure (e.g., ineffective, or the pictogram clearly links alcohol to mortality), (2) pregnancy warnings would have counterproductive effects (on women and the wider economy), (3) better alternatives exist (e.g., targeted prevention programs, prevention by health professionals). A large majority of the actors who spoke in the press came from the winegrowing sector. Conclusion This study fills a gap in the Anglosphere research on lobbying against alcohol warnings by analyzing lobbyists' arguments over a 20-year period covering both failed and successful industry lobbying. New findings have emerged that are likely related to the wine-oriented culture of France. In order to counter the alcohol lobbying practices we conclude with a number of public health recommendations.